Clinico-microbiological analysis of 121 patients with pulmonary Mycobacteroides abscessus complex disease in Japan – An NTM-JRC study with RIT. (December 2018) - Morimoto, Kozo; Nakagawa, Taku; Asami, Takahiro; Morino, Eriko; Fujiwara, Hiroshi; Hase, Isano; Tsujimoto, Yoshie; Izumi, Kiyohiko; Hayashi, Yuta; Matsuda, Shuichi; Murase, Yoshiro; Yano, Ryozo; et al.
Abstract: Rationale: No comprehensive analysis has previously been performed to evaluate the clinical aspects of and microbiological evidence associated with Mycobacteroides abscessus complex (MABC) infection in a region, such as Japan, with a low MABC incidence. Objectives: This study aimed to clarify the clinicopathological characteristics of MABC, which included clinical relatedness to erm (41) sequevar, phenotype (as colony morphology and minimum inhibitory concentration), and genotype. Methods: A total of 121 MABC patients (68 with M. abscessus subsp. abscessus and 53 with M. abscessus subsp. massiliense ) were recruited into this retrospective clinical-biological study from tertiary hospitals in Japan between 2004 and 2014. Results: Approximately 30% of MABC patients had a history of previous nontuberculous mycobacterium (NTM) disease. Furthermore, 24.8% of the patients had another concomitant NTM infection after they were diagnosed with MABC. Fewer than 10% of the patients in the M. abscessus group had T28C in erm (41). While we observed a higher conversion rate for M. massiliense than for M. abscessus (72.4% and 34.8%, respectively, p = 0.002), recurrence remained relatively common for M. massiliense (31.0%). In the M. abscessus patients, the MIC of clarithromycin (CLR) was significantly lower on day 3 in patients with a better treatment response than in refractory patients (The median MIC; 0.75 μg/ml v.s 2.0 μg/ml, p = 0.03). There was no significant relation between clinical manifestations and variable number of tandem repeat genotypes. Conclusions: Because the history and simultaneous isolation of other NTM in MABC infection are relatively common, these information should be carefully translated into clinical actions. The evaluation of early CLR resistance in M. abscessus and the erm (41) functions should be important to improve the treatment strategy. Highlights: Comprehensive clinico-microbiological data of M. abscessus compex pulmonary disease. History and simultaneous isolation of other NTM are relatively common. MIC of clarithromycin on day 3 could be associated with treatment response. No correlation with disease type or progression in VNTR and colony morphology.